Comparison of different methods of selection of stem cells from the pancreas to getting a culture - Ковпак, В. В.; Ковпак, О. С. (Scientific Progress & Innovations, 2018)
In the treatment of diabetes mellitus is particularly relevant to study the culture of cells derived from pancreatic tissue. However, the question of selected cells which could to adhesive and david, from this gland, is not studies enough. This, in turn, necessitates the development and comparison of various methods for the selection of stem cells from the pancreas in order to identify the optimal. That is why the purpose of our study was to compare different methods of disaggregation of the pancreas of the rat to obtain primary culture. To determine the optimal method for obtaining the culture of stem cells of the pancreas of the rat, we compared four methods treatment of tissue: collagenase treatment, warm trypsinization method, cold trypsinization method, modified explant method. The analysis of the results, was counting the number of cells, which carried out after formation a monolayer in one of the cups. On the third day of cultivation in Petri dishes revealed the appearance of single adhesive cells at use of the first three methods of disaggregation. For using the fourth method of disaggregation pancreatic tissue, was noted the appearance of adherent cells on the fourth–fifth day after sowing. However, it should be noted that the proliferation of cells was the highest in the use of the explant method. The least effective of the investigated methods was the treatment of pancreatic tissue 2 mg/cm3 collagenase. The number of cells in the 14th day of cultivation was 2.9 times lower compared to control (without the use of enzymes) and amounted to 216.3±12.4 thousand. With the use of the warm trypsinization method, the number of cells per 14th days of cultivation was 1.6 times smaller than that of the control and amounted to 385.0±16.2 thousand. The best effect of using the enzymatic processing of the pancreas was obtained using the cold trypsinization method. The number of cells per 14th days of cultivation when using this method was 475.0±27.9 thousand and was in 1.3 times lower compared to control. Analyzing the results of the study, it can be argued that the optimal method for obtaining the culture of stem cells of the pancreas of the rat is the modified method of explant. The number of cells per 14th days of cultivation was 627.3±9.7 thousand. This is significantly more compared with other investigated methods.